Surface settlement modelling using neural networks - Kori, Prajwal Jagadeesh (Nanyang Technological University, 2022)
Singapore is a highly urbanized and densely populated city with high-rise buildings and complex infrastructure above and below the ground. Hence, it is imperative that the ground movements induced from tunnelling operations are anticipated and controlled prior to their occurrence, which might otherwise produce undesirable consequences that can be catastrophic in nature and this may even extend to human lives.